Effectiveness of sediment basin and silt traps at oil palm plantations - Zainuddin, Nur Syahiza (2007)
In recent year, there has been an increasing comment over deterioration of water quality in many river systems in Malaysia. Therefore, this study analyse the effectiveness of implementing various types of sediment basin and silt trap in oil palm plantation located at Gua Musang. The district of Gua Musang is a major producer of oil palm plantation in Kelantan with the total area of 55 191 hectares. The aim of this study is to identify whether the water from this oil palm plantation be a part of contributor of the problem happened in Sg. Kelantan which is nowadays become shallow and polluted because of sedimentation problem. In this study there were three sediment basins has been analysed. A field measurement on suspended solid, turbidity and sediment loading was carried out before and after sediment basin. The range of Suspended Solid is between 5 mg/L to 50 mg/L before the sediment basins and 1 mg/L to 14 mg/L after sediment basins. Turbidity gives a result between 4.7 NTU to 79.0 NTU before the sediment basins and 5.8 NTU to 42.0 NTU after the sediment basins. From these data, total sediment loading per hectares was calculated and compared to the amount calculate by using USLE and MSLE formula. Beside that, the examination upon efficiency of sediment elimination was done and each sediment basin gave a result of 80%, 37.5% and 72%. However from questionnaire analysis on environmental awareness, the result shows that most developers and their workers awareness are still in moderate and low level.